2021
DOI: 10.1088/1361-6668/abfd0c
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen out-diffusion in REBCO coated conductor due to heating

Abstract: Rare earth barium copper oxide (REBCO) coated conductor has emerged as one of the high T c superconductors suitable for future ultrahigh field superconducting magnet applications. In the design and fabrication of such ultrahigh field REBCO magnets, it is essential to understand the behavior of REBCO coated conductor. The effect of heating on the properties of commercial REBCO coated conductors is very important for many practical reasons. Nevertheless, a comprehensive study on this effect hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Before concluding, we would like to mention that the external Cu layer might play a role in the thermally induced degradation of stabilized CCs. In particular, it has been shown that the Cu may act as a sink for oxygen atoms diffusing out of the RE BCO layer . Furthermore, we verified that annealing Cu-stabilized CCs in an O 2 atmosphere does not reduce the degradation of I c since the external Cu layer behaves as a barrier for the in-diffusion of oxygen atoms from the atmosphere.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Before concluding, we would like to mention that the external Cu layer might play a role in the thermally induced degradation of stabilized CCs. In particular, it has been shown that the Cu may act as a sink for oxygen atoms diffusing out of the RE BCO layer . Furthermore, we verified that annealing Cu-stabilized CCs in an O 2 atmosphere does not reduce the degradation of I c since the external Cu layer behaves as a barrier for the in-diffusion of oxygen atoms from the atmosphere.…”
Section: Discussionsupporting
confidence: 69%
“…The superconducting properties of the RE BCO, as T c and J c , are directly related to the oxygen content. ,, Therefore, the degradation of I c upon heating the CCs has been qualitatively ascribed to the activation of oxygen out-diffusion processes that modify the oxygen content of the RE BCO layer. ,,, If the oxygen diffusion alters the stoichiometry of the superconducting grains, one would expect a simultaneous variation of I c , T c , and of the c -axis parameter. However, a comparison of the results from Figures and points out that while a degradation of I c is already observed at T HT = 170 °C, neither ⟨ T c ⟩ nor T c onset varies before 220 °C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The soldering procedure for each joint was at about 210 °C, and lasted less than 15 min. Under this heating condition, the REBCO Ic degradation and the associated joint resistance rise should be small [11]. In addition, the joints were in low field region where the critical current is high, small degradation would not likely compromise the experiment.…”
Section: A the Simple-stacked Cable Samplementioning
confidence: 99%